QUASI Z-SOURCE NETWORK BASED CONTROL SCHEME FOR FSTP BLDC MOTOR (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The paper proposes a novel four switch three phase BLDC motor control scheme which boosts the voltage level, extends the range of speed as well as reduces output torque ripple. The additionally partial circuits of quasi Z-source network and the bridge arm of four-switch inverter constitute the quasi Z-source converter. During the operation of motor, shoot through states are inserted. Then the input voltage of inverter increases and the performance of motor can be markedly improved. The dynamic performance of current is influenced and the speed is limited, for the irregular dc-link voltage utilization in the control of four-switch three-phase (FSTP) BLDC motor. This project presents a novel topology, which combines quasi Z-source converter and FSTP drive circuit. The drawbacks of FSTP BLDC motor are analyzed, the control methods of each mode in quasi Z-source four-switch three-phase (QZFSTP) topology are illustrated. Simulations for QZFSTP BLDC motor were constructed in MATLAB/Simulink circumstance. We can provide an alternate strategy to control BLDC motor by using Four Switch Three Phase inverter. FSTPI helps reduction in switching losses, gate drive requirements, circuit cost and computational time. At low power application, FSTPI fed BLDC motor drives are more suitable than SSTPI (Six Switch Three Phase Inverter). Also reconfiguration of these three leg inverter to FSTPI, in case of switch or leg failure can be done. In proposed system losses are minimizing due to FSTPI because there is reduction in switching losses and also due to Quasi Z-source Inverter output voltage is boosting hence output results were better. To overcome the ripple in torque and distortion in current the QZFSTP BLDC motor control scheme is proposed.